Assessing the Contribution of Posidonia oceanica to Mediterranean Secondary Production Through Stable Isotope Analysis - Alan Deidun; Freja Azzopardi; Alessio Marrone; Alexia Massa-Gallucci; Karl Cutajar; Brian Hayden (Journal of Marine Science and Engineering)
The role of seagrasses in providing a complex habitat for marine organisms is globally documented; however, few studies have investigated the trophic incorporation of endemic Mediterranean Posidonia oceanica into marine food webs. Meadows of P. oceanica are declining due to climate change and anthropogenic pressures, emphasising the need to determine its contribution in local trophic dynamics. We investigated whether benthic marine invertebrate (BMI) and fish consumers assimilate carbon directly from P. oceanica seagrass or other sources along the seagrass meadow margins in Malta. We sampled and analysed the δ13C and δ15N isotope values of P. oceanica, particulate organic matter (POM), macroalgae, 14 invertebrate taxa, and 10 fishes at three locations marginal to P. oceanica seagrass meadows. Stable isotope ratios were significantly different between all taxa (F26 = 17.37, R2 = 0.68, p < 0.01) and locations (F2 = 34.22, R2 = 0.10, p < 0.01). The source, invertebrate, and fishes were enriched in both 13C and 15N at Baħar iċ-Ċagħaq relative to the other locations, L’Aħrax and Golden Bay, likely due to the increased effluent. Stable isotope mixing models were somewhat confounded as POM and macroalgae had similar δ13C and δ15N values at each site, hampering efforts to define the resource use of the sampled taxa. However, Posidonia oceanica made the lowest contribution for both consumer groups at all locations, consistent with the results of other Mediterranean studies, suggesting that P. oceanica does not contribute significantly to the diet of consumers at seagrass meadow margins within Maltese waters.